PERLINDUNGAN ANAK DARI PERKAWINAN SIRI BERDASARKAN PASAL 20 UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Supomo, Aris (Yustitia, 2017)
By the presence of a child born from a legal marriage (marriage recorded) both of his parents have proven that the child is a legitimate biological child of his father and mother. The legal consequences if the marriage is not recorded (generally known as "siri marriage"), the status of the child born from the marriage will be uncertain, because the marriage of both parents is only religiously valid. Based on Article 20 of Law Number 35 of 2014 concerning Child Protection. This research is done by using normative juridical method. This juridical approach is due to this research by analyzing the legal aspects that exist, and is normative since this study focuses more on the analysis of existing legislation and other regulations, both from national and international perspectives, as well as using data secondary data that is scientific references or other scientific writings as a study material that can support the completeness of this scientific work To find out, analyze and describe, Protection of Children from Siri Marriage Based on Article 20 of Law Number 35 of 2014 concerning Child Protection and the Government's Role on the Protection of Children from Siri Marriage Based on the law. This theory of justice contains a demand that people treat each other according to their rights and obligations, such treatment is indiscriminate or favoritism, but, everyone is treated equally according to their rights and obligations. Justice is fundamentally described by Aristotle in the fifth book of the Nicomachean Ethics book. To find out about justice and injustice must be discussed three main things, namely (1) what actions are related to the term, (2) what is the meaning of justice, and (3) between two extreme points whether justice is located.